Iron-induced parafibrin formation in tumors fosters immune evasion - Lipinski, Boguslaw (Landes Bioscience, 2014)
Although efficacious in vitro, it is well known that adoptive immunotherapeutic modalities lose their potency when applied in vivo. Furthermore, malignant cell exposure to blood platelets attenuates the anticancer activity of natural killer (NK) cells. We argue that upon contact with redox iron, fibrinogen is converted to a hydrophobic fibrin-like polymer that coats tumor cells and provides protection from immune-mediated destruction.